If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + 3b + -2c = 7 Solving a + 3b + -2c = 7 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. a + 3b + -3b + -2c = 7 + -3b Combine like terms: 3b + -3b = 0 a + 0 + -2c = 7 + -3b a + -2c = 7 + -3b Add '2c' to each side of the equation. a + -2c + 2c = 7 + -3b + 2c Combine like terms: -2c + 2c = 0 a + 0 = 7 + -3b + 2c a = 7 + -3b + 2c Simplifying a = 7 + -3b + 2c
| -9.3=B-3.4 | | x^3-x^2y-4x+y^3+xy^2-4y=0 | | y-2z=-2 | | 13d-5d=16 | | -35=5y+5 | | x-y+3z=30 | | x^3-x^2y+xy^2+y^3-4x-4y=0 | | 2.15x=x+250 | | -(4XY-8)+2(4XY+6)= | | 2.5x=x+250 | | -2.9=F+3.8 | | x^2+31x+72=0 | | -0.5+K=4.3 | | 8/(5x-6) | | x=3.1415926-x | | 2x=x+250 | | f(x)=8/(5x-6) | | 11x+13y=-19 | | K(x)=9logx+8 | | 6-(10x-2)^1/3 | | 4-(6x-5)=-3(x+2)+7 | | (3x^2)-3.4x+0.16=0 | | 7x+10.5y=252 | | 57+3x=6x-7 | | -5(x+3)=4x-5 | | -(7k-4)-k=10k-2 | | b^2-8b-84=0 | | (4-y^2)dx-(4-x^2)dy=0 | | 4x-3=-5x-7 | | 1.7x=x+250 | | .25+176+54= | | 33x=528 |